Identifikasi Fitokimia Senyawa Alkaloid Daun Kedondong (Spondias dulcis) dengan Metode Ektraksi Maserasi - Riati Yulia Emanuel Awusi; Andi Ganang D (Universitas Widya Nusantara, 2025)
Spondias dulcis (commonly known as ambarella or kedondong) is a tropical plant traditionally used as herbal medicine. Its leaves are known to contain various secondary metabolites, including alkaloids, which may possess important pharmacological activities. This study aimed to identify the presence of alkaloid compounds in kedondong leaves using the maceration extraction method. The samples were prepared by drying the leaves, grinding them into powder, and extracting with 96% ethanol through maceration for 3 × 24 hours. The obtained extract was subjected to phytochemical screening using Mayer, Wagner, Dragendorff, and Bouchardat reagents. The results revealed specific precipitate formations in all reagents, namely yellowish-white (Mayer), reddish-brown (Wagner), orange (Dragendorff), and dark brown (Bouchardat), indicating a positive presence of alkaloids. Therefore, it can be concluded that kedondong leaves contain alkaloid compounds and that maceration is an effective method for their extraction. These findings support the traditional use of kedondong leaves and highlight their potential as a source for herbal medicine development.